Development of a compact continuous-flow electrochemical cell for an energy efficient production of alkali - Mehmood, Asad; Jang, Eunjin; Lee, Nakwon; Jung, Kwang-Deog; Ha, Heung Yong (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
In this study, we report development of a compact continuous-flow electrochemical cell for an energy-efficient splitting of brine (aqueous NaCl) to yield alkali (NaOH) that would be used for sequestration of carbon dioxide into carbonate minerals at a subsequent stage. Herein, at the first step of process development, cell design and electrode structures are optimized for producing NaOH with minimum input energy. Two cell designs representing a primitive version (design 1) and an advanced version (design 2) are evaluated. The advanced structure of electrochemical cell with a thinner middle compartment exhibits up to 300% improvement in output current density as compared to the primitive version due to shorter ionic diffusion paths. Structural modifications of the anode lead to a successful reduction of Pt loadings by an appreciable amount of 75% without compromising the cell performance. Pt black as a cathode catalyst shows a significantly better performance stability as compared to Pt/C, which experiences a sharp performance decline in a 50 h steady-state operation. It has been demonstrated that the compact structure of electrochemical cell allows use of a highly diluted NaOH solution (0.1 M) as catholyte without deteriorating the cell performance and stability. Finally, caustic efficiency and different figures of merit are calculated. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: CARBON-DIOXIDE; CO2 CAPTURE; CONVERSION; FORMATE; VOLTAGE; LAYER